Budd-Chiari syndrome in childhood: presentation of 13 cases - Koçak, Nurten; Özsoylu, Şinasi; Göğüş, Safiye (The Turkish Journal of Pediatrics, 1978)
13 cases of Budd-Chiari syndrome are presented, etiological, clinical, histopathological and laboratory findings are discussed and related literature is reviewed.